The Effect of COVID-19 Pandemic on Service Sector Sustainability and Growth - Xiang, Shihui; Rasool, Saad; Hang, Yong; Javid, Kamran; Javed, Tasawar; Artene, Alin Emanuel (Frontiers in Psychology, 2021)
Coronavirus disease (COVID-19) is having an unprecedented and unpredictable impact on the world's economy. The pandemic has driven the world toward adapting to the current circumstances regardless of the business, sector, or industry. The coronavirus epidemic (COVID19) has affected the global economy and service sector. The purpose of the current study is to assess the effect of COVID-19 on service sector growth and sustainability. Global sectors and industries are trying to anchor themselves amidst the pandemic. The study focuses on the sectors that are badly hit by the outbreak and discussed the strategies and responses different countries are taking to sustain their economies. This study concludes that the vital role of Information Technology and digitization supports the economies in their fight against the pandemic and helps them sustain themselves amid crises. This study also contributes to the body of literature by suggesting IT-based solutions for various industries to elevate effective responsiveness and avoid significant losses.